Characterization of polyphenols and evaluation of antioxidant capacity in grape pomace of the cv. Malbec - Antoniolli, Andrea Noelia (2015)
Low molecular weight polyphenols (LMW-PPs) and anthocyanins, along with the antioxidant capacity, were assessed in grape pomace extract (GPE) of red grape (Vitis vinifera L.) cv. Malbec. Twenty-six phenolics (13 LMW-PPs and 13 anthocyanins) were characterized and quantified by HPLC-MWD and UPLC?ESI-MS. The maximum concentrations of LMW-PPs corresponded to the flavanols (+)-catechin and ()-epicatechin, whereas malvidin-3-glucoside was the most abundant anthocyanin. Piceatannol, a stilbene analogue to resveratrol with higher antioxidant activity, was firstly identified and quantified in GPE of the cv. Malbec. The antioxidant activity for Malbec GPE determined by oxygen radical absorbance capacity (ORAC) assay was 2756 lmol TE g1 GPE. Therefore, the data reported sustain the use of winemaking by-products as a cheap source of phenolic compounds suitable for biotechnological applications, as a strategy for sustainable oenology.